meta-analysis of preference-performance relationships in phytophagous insects - Gripenberg, Sofia; Mayhew, Peter J; Parnell, Mark; Roslin, Tomas (Ecology letters, 2010)
Ecology Letters (2010) 13: 383-393 The extent to which behavioural choices reflect fine-tuned evolutionary adaptation remains an open debate. For herbivorous insects, the preference-performance hypothesis (PPH) states that female insects will evolve to oviposit on hosts on which their offspring fare best. In this study, we use meta-analysis to assess the balance of evidence for and against the PPH, and to evaluate the role of individual factors proposed to influence host selection by female insects. We do so in an explicitly bitrophic context (herbivores versus plants). Overall, our analyses offer clear support for the PPH: Offspring survive better on preferred plant types, and females lay more eggs on plant types conducive to offspring performance. We also found evidence for an effect of diet breadth on host choice: female preference for 'good quality plants' was stronger in oligophagous insects than in polyphagous insects. Nonetheless, despite the large numbers of preference-performance studies conducted to date, sample sizes in our meta-analysis are low due to the inconsistent format used by authors to present their results. To improve the situation, we invite authors to contribute to the data base emerging from this work, with the aim of reaching a strengthened synthesis of the subject field.